Improved Cardiometabolic Health Using a Personalised Nutrition Approach: The ZOE METHOD Study - Kate M. Bermingham; Inbar Linenberg; Lorenzo Polidori; Jonathan Wolf; William J. Bulsiewicz; Tim D. Spector; Sarah E. Berry (Proceedings)
Background: Large variability exists in people’s responses to foods [...]